2013
DOI: 10.1158/1055-9965.epi-12-0570
|View full text |Cite|
|
Sign up to set email alerts
|

Which Risk Model to Use? Clinical Implications of the ACS MRI Screening Guidelines

Abstract: The American Cancer Society (ACS) guidelines define the appropriate use of MRI as an adjunct to mammography for breast cancer screening. Three risk assessment models are recommended to determine if women are at sufficient risk to warrant the use of this expensive screening tool, however, the real-world application of these models has not been explored. We sought to understand how these models behave in a community setting for women undergoing mammography screening. We conducted a retrospective analysis of 5,89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 11 publications
2
30
0
1
Order By: Relevance
“…Women in these risk categories constitute a small percentage of all women. In 2014, there were an estimated 3,088,180 female survivors of invasive breast cancer 40 years of age and older, approximately 4% of the total population; 14 a 2005 prevalence estimate of those having received a diagnosis of in-situ breast cancer was 570,403, expected to increase to over 1 million by 2016; 15 0.2 to 0.3 percent of the general population and 2 percent of Ashkenazi Jewish women are estimated to be carriers of the BRCA1 or BRCA2 mutation, 16 and overall 5.8% of mammography screening age women may be either known or suspected mutation carriers based on having approximately a 20% or greater lifetime risk of breast cancer based on assessment of family history with specialty software; 17 and in 2010 it was estimated that there were 50,000 to 55,000 women in the U.S. who had been treated with moderate to high-dose chest radiation for pediatric and young adult cancers. 18 There also are women outside of these risk categories who are still at higher than average risk of breast cancer and for whom mammography alone may be less effective, including women with significant family histories but who do not have a high probability of being carriers of identified mutations, 19 women with a prior diagnosis of benign proliferative breast disease, 20 and women with significant mammographic breast density.…”
Section: Questions Guiding the Evidence Reviewmentioning
confidence: 99%
“…Women in these risk categories constitute a small percentage of all women. In 2014, there were an estimated 3,088,180 female survivors of invasive breast cancer 40 years of age and older, approximately 4% of the total population; 14 a 2005 prevalence estimate of those having received a diagnosis of in-situ breast cancer was 570,403, expected to increase to over 1 million by 2016; 15 0.2 to 0.3 percent of the general population and 2 percent of Ashkenazi Jewish women are estimated to be carriers of the BRCA1 or BRCA2 mutation, 16 and overall 5.8% of mammography screening age women may be either known or suspected mutation carriers based on having approximately a 20% or greater lifetime risk of breast cancer based on assessment of family history with specialty software; 17 and in 2010 it was estimated that there were 50,000 to 55,000 women in the U.S. who had been treated with moderate to high-dose chest radiation for pediatric and young adult cancers. 18 There also are women outside of these risk categories who are still at higher than average risk of breast cancer and for whom mammography alone may be less effective, including women with significant family histories but who do not have a high probability of being carriers of identified mutations, 19 women with a prior diagnosis of benign proliferative breast disease, 20 and women with significant mammographic breast density.…”
Section: Questions Guiding the Evidence Reviewmentioning
confidence: 99%
“…The question of which risk model to use in the family history setting is a problem, as the models often give quite different read-outs. 73,74 To our knowledge there has been only one other assessment of breast cancer risk prediction in the family history setting, this time in North America, which again showed that TC substantially outperformed the Gail model. 75 In this study, the Gail model, as in our original series, 57 predicted cancer rates half of those that actually occurred.…”
Section: Discussionmentioning
confidence: 94%
“…There are discrepancies in the reporting of lifetime risk of breast cancer as reported by Ozanne et al who demonstrated inconsistency in three familial-based risk models that put women in different categories with differential overlap. 29 …”
Section: Discussionmentioning
confidence: 99%